Linear programming for aggregate production planning in a textile company (2018)
This article aims to propose and implement an aggregated production planning model to provide optimal strategies in the medium term for a textile company, for which a linear programming model is proposed to minimise total costs associated with labour and inventory levels. The model proposed takes into account characteristics associated with fabric contraction, wastes in the process, the efficiency of new employees, and training requirements. The model is implemented and solved in GAMS, supported on an MSExcel interface, to find the optimal solution, which is to apply a hybrid strategy to the production plan, and also some strategies for improving the production process are generated. © 2018, Institute of Biopolymers and Chemical Fibres. All rights reserved.